MANAJEMEN JARINGAN INTERNET MENGGUNAKAN MIKROTIK DI PONDOK PESANTREN EL-BAYAN - Nugroho, Fajar; Aulia, Dina; Rizal Fadli, Fahri (Jurnal Teknologi dan Bisnis, 2022)
Practical Work is a subject that must be taken by students. In fulfilling the author’s obligation to make this Practical Work Report as one of the requirements for graduation from the STMIK Kompuama Majenang Information Systems Study Program. The purpose of writing this practical work report is to find out the management of the internet network at the El-Bayan Islamic Boarding School. The research method used by the author in the field study includes two procedures, namely the method of data collection and implementation of work programs. From this analysis and observation, it is known that the El-Bayan Islamic Boarding School provides internet network facilities that are used by students who are students. However, in its use it is still not managed which causes the internet to become unstable due to the large number of unfair uses (exceeding the limit) by students. To manage usage, Mikrotik is an effective alternative, so it is hoped that it will bring order to the use of the internet to be wiser.